2009
DOI: 10.1177/1062860609332512
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Handoff Mnemonics Literature

Abstract: A systematic review of published English-language articles on handoffs is conducted (1987 to June 4, 2008). Forty-six articles describing 24 handoff mnemonics are identified by trained reviewers. The majority (82.6%) have been published in the last 3 years (2006-2008), and SBAR (Situation, Background, Assessment, Recommendation) is the most frequently cited mnemonic (69.6%). Of 7 handoff research articles, only 4 study mnemonics. All 4 of these studies have relatively small sample sizes (10-100) and lack valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
194
0
12

Year Published

2012
2012
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 306 publications
(208 citation statements)
references
References 31 publications
(21 reference statements)
2
194
0
12
Order By: Relevance
“…However, a systematic review conducted between 1987 and 2008 identified 24 mnemonics reported in the literature and found that more than half of the studies used "SBAR" (situa tion, background, assessment, recommendations). 12 This clearly indicates that there is no single mnemonic that can fit each situation and specialty. Moreover, these mnemonics were not validated on a larger scale.…”
Section: Discussionmentioning
confidence: 99%
“…However, a systematic review conducted between 1987 and 2008 identified 24 mnemonics reported in the literature and found that more than half of the studies used "SBAR" (situa tion, background, assessment, recommendations). 12 This clearly indicates that there is no single mnemonic that can fit each situation and specialty. Moreover, these mnemonics were not validated on a larger scale.…”
Section: Discussionmentioning
confidence: 99%
“…78 Despite the recognized need for standardized tools and procedures at each site, the ACGME recognizes that each site may have different needs and will not use the same templates or tools. 68 ToC concepts apply to practitioners beyond the training period. With the use of learner-identified ToC milestones, a longitudinal education and evaluation curriculum that uses tool-and simulation-based education modules has been developed for all levels of learners, from medical student through faculty.…”
Section: Teaching Tocsmentioning
confidence: 99%
“…The SBAR (situation, background, assessment, recommendations) is the most commonly mentioned in the bibliography, but no robust studies have demonstrated the usefulness of any of the currently used rules. 18 In some fields requiring a high precision, such as air traffic control, strict and systematic rules are followed in each change of shift. 19 One study analyzed the change of shift in relation to tasks where failure could lead to severe consequences.…”
Section: Discusssionmentioning
confidence: 99%